2015
DOI: 10.1016/j.jtcvs.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch geometry after the Norwood procedure: The value of arch angle augmentation

Abstract: Arch angle augmentation with glutaraldehyde-treated autologous pericardium in the Norwood procedure creates more aortopulmonary space with a smoother arch angle and diminished incidence of postoperative recoarctation, bronchial compression, or branch pulmonary artery compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 33 publications
1
25
1
Order By: Relevance
“…The incidence of arch reintervention of any type was very low. The exceptionally low recoarctation rate of 4.1% is similar to the results shown after shorter follow-up 12,13,24 and emphasizes both the effectiveness of the interdigitating technique and the longevity of this type of repair with regard to the distal anastomosis. It has been previously shown that recoarctation is caused by residual ductal tissue and insufficient distal patch augmentation.…”
Section: Reintervention and Recoarctationsupporting
confidence: 76%
See 1 more Smart Citation
“…The incidence of arch reintervention of any type was very low. The exceptionally low recoarctation rate of 4.1% is similar to the results shown after shorter follow-up 12,13,24 and emphasizes both the effectiveness of the interdigitating technique and the longevity of this type of repair with regard to the distal anastomosis. It has been previously shown that recoarctation is caused by residual ductal tissue and insufficient distal patch augmentation.…”
Section: Reintervention and Recoarctationsupporting
confidence: 76%
“…Avoiding the risk of obstruction by excessive patching comes with a higher risk of complications due to kinking or external compression of adjacent structures and cannot be advised unequivocally. This compromising effect has been highlighted by Hasegawa et al 24 recently, as they showed the importance of adequate aortopulmonary space to reduce reintervention rates. Achieving adequate but not excessive patching in each patient is challenging, and there is not a standard technique available that can guarantee success.…”
Section: Reintervention and Recoarctationmentioning
confidence: 90%
“…The thick-walled fragile ductal tissue was completely excised until the normal thin wall of the Kommerell diverticulum appeared, and a glutaraldehydetreated autologous pericardial (GA-AP) patch was sutured to the inferior wall of the Kommerell diverticulum to augment the lesser curvature of the newly reconstructed aortic arch. 1 On cardiac arrest, the transected ascending aorta was anastomosed side-by-side to the transected main pulmonary artery, and this amalgamation was joined to the Kommerell diverticulum with the GA-AP patch (Figure 2, B). After the distal end of the right aortic arch was divided and the superior wall of the Kommerell diverticulum was opened longitudinally, this continuity from the neoaortic root to the descending aorta was anastomosed to the longitudinally opened aortic arch (Figure 2, C).…”
Section: Clinical Summarymentioning
confidence: 99%
“…Examples include the detection of anatomical abnormalities [1] , preoperative planning and follow-up of patients with cardiovascular diseases [2][3][4] , risk prediction associated with atherosclerosis development [5][6][7][8] , and cardiovascular devices design support [9] . In particular, morphometry-based analysis finds massive adoption for current research of mapping the effects of natural aging on the structural and functional properties of the aorta [10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%